Endothelial Cell-Derived TGF-β Promotes Epithelial-Mesenchymal Transition via CD133 in HBx-Infected Hepatoma Cells - Rawal, Preety; Siddiqui, Hamda; Hassan, Mohsin; Choudhary, Manish Chandra; Tripathi, Dinesh M.; Nain, Vikrant; Trehanpati, Nirupama; Kaur, Savneet (Frontiers in Oncology, 2019)
Background: Hepatitis B-X Protein (HBx) encoded in Hepatitis B virus (HBV) is known to play a critical role in development and progression of HBV induced hepatocellular carcinoma (HCC). HBx interacts and activates various cells in HCC microenvironment to promote tumor initiation, progression and invasion. In this study, we investigated how surrounding stromal cells interact with HBV-infected hepatoma cells by a series of in vitro co-culture studies. Methods: Huh7 hepatoma cells were cultured and transfected with the mammalian expression vector pGFP-HBx. Co-culture assays were performed between HBx-transfected Huh7 cells and conditioned media (CM) from stromal cells [endothelial cell lines (HUVECs) and hepatic stellate cell lines (LX-2 cells)]. The effect of these interactions was studied by a series of functional assays like chemotaxis, invasion and wound healing scratch assays. Also, quantitative real time (RT)-PCRs of the mesenchymal genes was performed in the hepatoma cells with and without the co-cultures. Hep3B cells with an integrated HBV genome were taken as positive controls for some of the assays. Results: HBx-transfected Huh7 cells cultured in presence of CM from HUVECs illustrated enhanced migration and tube formation as compared to HBx-transfected cells cultured alone or co-cultured with LX-2 cells. HBx-transfected hepatoma cells incubated with CM from HUVECs also expressed mesenchymal genes including Thy1, CDH2, TGFβR1, VIM and CD133. To evaluate factors in CM from stromal cells, ELISAs revealed increased levels of TGF-β in CM from HUVECs. In comparison to unstimulated HBx-transfected Huh7 cells, TGF-β stimulated cells displayed increased invasive properties and mesenchymal gene expression. RT-PCR and flow cytometry analysis further demonstrated that incubation with either CM from HUVECs or TGF-β significantly increased the expression of a stemness marker, CD133 in HBx-infected hepatoma cells. Gene inhibition experiments with CD133 siRNAs showed a downregulation of mesenchymal gene expression and properties in TGF-β induced HBx-infected hepatoma cells as compared to control siRNA treated cells, indicating CD133 as one of the key molecules affecting epithelial to mesenchymal transition (EMT) in HBV-infected cells. Conclusion: The study indicates that the secretory factors like TGF-β from neighbouring endothelial cells enhance expression of CD133 and impart an aggressive EMT phenotype to HBx-infected hepatoma cells.